2009
DOI: 10.1007/s11270-009-0276-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Degradation of Pentachlorophenol Using Microwave-Induced Nanoscale Fe0 and Activated Carbon

Abstract: Microwave (MW) is applied to enhance pentachlorophenol (PCP) removal using zerovalent iron (ZVI, Fe 0 ) or granular activated carbon (GAC) as the dielectric media. Applying MW energy at 700 W for 20 s, the results show that Fe 0 is capable of enhancing the CB removing 2.7 times (91% vs. 34 %) than GAC. Because Fe 0 has higher dielectric loss (39.5 F/m vs. 8.3 F/m), it absorbs more MW energy to speed up the oxidation rate resulting in a faster temperature rise than GAC. Thus, in the presence of MW, Fe 0 is supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…23). In this study, the HPLC spectra and COD results showed a similar trend in mineralization and the lack of toxic intermediates and by products [ 28 , 39 ].…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…23). In this study, the HPLC spectra and COD results showed a similar trend in mineralization and the lack of toxic intermediates and by products [ 28 , 39 ].…”
Section: Resultsmentioning
confidence: 73%
“…Also synergetic factor of MW in MW/SPS and MW/H 2 O 2 was 6.6 and 13.75 respectively. This factor shows that MW process have higher synergetic effect on H 2 O 2 decomposition than SPS [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Selecting an appropriate medium to absorb the MW energy in order to integrate MW treatment technology has been studied by researchers in various technological and scientific fields, because MW irradiation is known to enhance various reaction kinetics owing to its rapid and homogeneous heating (Park et al, 2000;Menéndez et al, 2002;Takashima et al, 2008). For example, using MW energy-absorbing media with various absorption capacities, for example, granular activated carbon, ZVI, copper, and selected catalysts, has been studied for treating aqueous pentachlorophenol (Liu et al, 2004;Jou, 2008;Jou and Wu, 2008;Lee et al, 2009b), chlorobenzene (CB) (Lee et al, 2009aJou et al, 2010), and P-Chlorophenol (Zhao et al, 2010) or improving the reaction rate of TiO 2 photocatalyst ( Jou et al, 2008;Mishra et al, 2010) in order to save energy consumption and improve treatment efficiency (Liu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Successful application of MW technology depends on selecting appropriate media for treating organic matter including microwave combined with granular activated carbon or zero-valent iron nano-particles for treating pentachlorophenol Jou & Wu, 2008;H. Lee, C. Lee, & Jou, 2010a) and improving the efficiency of TiO 2 photocatalyst (Jou, Lee, Tsai, & Wang, 2008) to save energy while improving efficiencies (Liu, Quan, Bo, Chen, & Zhao, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Lee, C. Lee, & Jou, 2010a) and improving the efficiency of TiO 2 photocatalyst (Jou, Lee, Tsai, & Wang, 2008) to save energy while improving efficiencies (Liu, Quan, Bo, Chen, & Zhao, 2004). Lee et al (2009b; and Jou et al (2010a; applied MW radiation induced zero-valent iron nano-particles for enhancing the CB decomposition; the results show that when MW radiation penetrates the solution to reach the surface of suspended Fe 0 particles, the radiation accelerates the iron oxidization, and increases the surface activity site thus enhancing the CB decomposition rate (Lee, Jou, & Huang, 2009b;Lee, Jou, & Wang, 2010b;Jou, Lee, Lin, & Huang, 2010a;Jou, Wu, & Lee, 2010b).…”
Section: Introductionmentioning
confidence: 99%